Innate Immune Function of Mitochondrial Metabolism - Sancho, David; Enamorado, Michel; Garaude, Johan (Frontiers in Immunology, 2017)
Sensing of microbe-associated molecular patterns or danger signals by innate immune receptors drives a complex exchange of information. Innate receptor signalling triggers transcriptional events, but also induces profound changes in metabolic fluxes, redox balance and metabolite abundance thereby influencing immune cell function. Mitochondria are at the core of metabolic adaptation to the changing environment. The close interaction between mitochondrial metabolism and immune signalling has emerged as a central regulator of innate sensing. Metabolic processes generate a constant flow of electrons that eventually end up in the mitochondrial electron transport chain (ETC). Two electron carriers and four respiratory complexes that can assemble as larger molecular supercomplexes (SCs) compose the ETC in the mitochondrial inner membrane. While the meaning and biological relevance of such structural organisation is a matter of passionate debates, recent data support that innate stimuli remodel the ETC. We will review the function of mitochondrial metabolism and ETC dynamics as innate rheostats that regulate signalling, transcription and epigenetics to orchestrate innate immune responses.